ANALISIS RISIKO KELELAHAN FISIOLOGIS DAN MUSCULUSKELETALDISORDERS (MSDS) PADA PEKERJA BENGKEL PENGECATAN MOBILINFORMAL DENGAN METODE BASELINE RISK IDENTIFICATION OFERGONOMIC FACTORS (BRIEF) DAN QUICK EXPOSURE CHECKLIST (QEC) - Apdila Restisha, Vanny
One of the industries that has fatigue potential and musculoskeletal disorders (MSDs) to its workers is informal car painting workshop. In addition to the fatigue, workers at car painting workshop also has a potential risk of physical dangers in terms of back pain, elbow, and others. The purpose of this study is to identify and determine the effect of the means, stance, posture and working position of informal car painting worker who has risk of MSDs using the Baseline Risk Identification of Ergonomic Factors (BRIEF) and the Quick Exposure Checklist (QEC) methods, also to determine the level of fatigue of workers objectively and subjectively. Objective fatigue is viewed from the changes of pulse, blood pressure, body temperature, and reaction time before work (08:am) and after work (04:00 pm), while subjective fatigue is viewed from Questionnaire of Measure Tool of Fatigue Feelings of Works. Workplace climate measurement shows that the climates meet the Threshold Limit Values based on Indonesian Health Minister’s Decision No. 1405/MENKES/SK/XI/2002. Risk of ergonomic measurement shows that further investigation of body position and treatment will be needed in near future. There are significant differences on blood pressure, pulse, and body temperature before and after work. Based on the results of statistical tests, the most dominant factor affecting systolic blood pressure are age, Body Masaa Index (BMI), and smoking habits. Toxic chemicals in cigarettes causes narrowing of the blood vessels, so the heart must pump blood stronger, which causes increased pressure in the blood vessels. Factors affecting diastolic blood pressure and pulse rate are BMI, a person who has a body size including obesity allows an increase in blood pressure. The dominant factor that affecting body temperature is the smoking habit.